MODELING AND SIMULATION ANALYSIS OF AIRCRAFT MAINTENANCE OPERATIONS - Abdulmalek, Fawaz; Savsar, Mehmet (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
This study examines a specific airline’s aircraft maintenance operations and proposes three modeling and analysis methodologies for maintenance-related issues. To determine if standard maintenance times should be multiplied by suppliers and company factors to calculate the permissible times for the technicians, a set of hypotheses is first formulated and tested. Second, four elements that affect aircraft maintenance delays are identified at various levels, and associated data is collected using work measurement techniques. The data is then examined by the Design of Experiments (DOE) to determine the factors that most significantly affect the delays in maintenance operations. Third, a comprehensive and detailed simulation model is developed to evaluate alternative scenarios that could improve maintenance operations and reduce maintenance cycle times. The optimum options are selected, which shorten maintenance cycles and increase resource utilization. For aircraft maintenance engineers and operations managers, the modeling approaches and results presented in this study might be valuable in analyzing and improving their systems.